Efektifitas Penggunaan Modul Berbasis Budaya Lokal Minangkabau Untuk Meningkatkan Ketahanan Budaya Siswa Kelas IV SD - Anastasha, Desty Ayu; Lasari, Yufi Latmini (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2023)
The Minangkabau Local Module is a teaching module developed by researchers. This research aims to increase students' cultural resilience in the learning process and determine the level of effectiveness of using modules on student competence in mastering material and cultural resilience. It is hoped that the modules used can be used effectively by students to improve their cultural adaptation abilities. To test this effectiveness, research was conducted on Class IV students at SDN 02 Pariangan. Effective results can be seen in the implementation of the Pancasila student profile module with the theme of a sustainable lifestyle. At each stage of implementation, students develop cultural adaptation abilities according to expectations based on the values of the Pancasila student profile.